The Role of Mediation Capital Expenditures on the Relationship between Regional Original Income and Regional Financial Performance Growth: Empirical Evidence Panel Data in Aceh - Surna Lastri; Marlizar Marlizar; Maidar Maidar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The main objective of this study is to examine the mediating role of capital expenditures on the effect of local revenue on the growth of regional financial performance. Data collection uses secondary data obtained from the Financial Supervisory Agency (BPK) Audit Results Report (LHP) in the Financial Reports of City Districts in Aceh Province for period 2015-2019. The population in this study includes all districts/cities in Aceh Province, totaling 23 districts/cities from 2015-2019, with the number of samples taken using the census sampling technique as many as 23 districts/cities. Technical data analysis using panel data regression with the help of Eviews 10 software and Microsoft Office Excel 2019. This study indicates that regional original income has a significant effect on capital expenditure and capital expenditure also has a significant effect on financial performance growth. Capital expenditures can mediate local government revenue on the growth of regional financial performance. Original regional income does not directly affect the improvement of regional financial performance in districts/cities in Aceh Province. This study uses capital expenditure as a mediating variable on the effect of original local government revenue on improving regional financial performance. In contrast, previous studies used capital expenditure as an endogenous variable on regional financial performance. This research recommends to the district/city governments in Aceh province to increase continuously local revenue by optimizing the potential of natural resources, human resources, and capital resources.